Rehabilitation of landfill by using Phytoremediation approach to become a Community Green Area : case study at Worldwide Landfills Park, Air Hitam, Puchong, Selangor / Nur Aniyah Nazurah Samad - Samad, Nur Aniyah Nazurah (2018)
Rehabilitation can be simply defined as restoring the land to better condition. For this study, it will rehabilitate the former landfill site of Worldwide Landfills Park towards community green area by enhancing and providing a solution for the stated issues. The physical character will be emphasized on the function of green spaces, linkages between spaces and solving the environmental concerns. The methodology of this study involves the implementation stages of secondary data from a government department and existing data from previous researchers which have been published. The primary data has been identified through observation and data recorded method. The data collected are synthesized to identify the potential area to be developed and preserved. Based on the strategy and design ideas inspired by the concept of Reverse Inverse that has been transformed into a physical form in designing the green spaces to be more functional, good linkages between spaces and better solution for environmental issues make the pace more functional and lively with its own identity following the concept. Engaging the public with nature will give opportunities to learn and educate them throughout outdoor activities. Hopefully, this project can be used as design strategies and guidelines for stakeholders in rehabilitating the former landfill site to create a place that has inter-relation between human and landscape.